Crafting A Sustainable Environment For Women Journalists In Arunachal Pradesh: A Way Forward (International Journal of Food and Nutritional Sciences, 2023)
India has always been referred to as being the flag bearer of democracy world over. And with the rising population and surpassing China as being the most populated country in the world according to the United Nations latest reports, India has failed miserably in the field of journalism in recent times. And for a country of such proportion and stature deserves a media that would be able to uphold the rights of the people to information through a system that is free of corruption, manipulation and most of all free of censorship. The Indian journalistic space has seen huge strides being taken in regards with the inclusion of women in the field of journalism. Technologically driven, the Indian media now have surpassed physical boundaries and with the digital media systems, have brought about profound changes in the nature and organisation of contemporary communications. However, India's press freedom dropped eight places from the previous year to 150 out of 180 nations in the 2022 edition of Reporters Without Borders' (2019) Press Freedom Index.